Aspek Kimia Dan Nilai Energi Susu Goreng Berbahan Dasar Susu Sapi Dengan Plain Yogurt Sebagai Koagulan - Lay, Inggrid E.; Sipahelut, Geertruida M.; Riwu, Agustinus R.; Armadianto, Heri (Yayasan Sumber Daya Manusia Cerdas, 2024)
Fried milk is a traditional dairy product originating from one of the district in East Nusa Tenggara, namely Rote Ndao regency which is made from buffalo milk and palm sugar which is sold in several industrial centers in Lobalain district This study aims to determine the effect of the use of a combination of crude papain and plain yogurt as an acidifying agent on the chemical aspects and energy value of the fried milk made from cow’s milk. The method used is a complete randomized design (CRD) consisting of 4 treatments amd 4 repeats. The treatment consist of P1: crude papain 0,5% + plain yogurt 1% of milk volume, P2: crude papain 0,5% + 1,5% plain yogurt of milk volume, P3: crude papain 0,5% + Plain yogurt 2% of milk volume, P4: crude papain 0,5% + Plain yogurt 2,5% of milk volume. The variables studied include, water content, protein, fat, sugar, calcium, lactose and calories. The data obtained were analyzed using Analysis Of Variance (ANOVA) followed by Duncan Multiple Range Test (DMRT) to determine the effect between treatments. The results showed that the addition of papaya sap and plain yogurt enzymes had an intangible effect (P>0,05) on Protein, Fat, Sugar, Lactose and Calcium of fried milk, a real effect (P<0,05) on the water content of fried milk, and very real effect (P<0,01) on fried milk calories. It was concluded that the use of crude and plain yogurt increased the water content and calories of fried milk along with increasing level of plain yogurt use.